Investigation of Nitramine‐Based Amorphous Energetics. Issue 1 (8th October 2015) - Stepanov, Victor; Patel, Rajen B.; Mudryy, Ruslan; Qiu, Hongwei
Abstract: To date, the use of high explosives (HEs) has been largely limited to their crystalline forms. The glassy forms of these materials have not received much attention. While the highest density and stability of HEs is only attainable in the crystalline state, the unique properties exhibited by glasses may offer significant practical advantages. In this work, the production and properties of glassy molecular dispersions based on CL‐20 with HMX and polyvinyl acetate additives were investigated. The glassy form was achieved by rapid precipitation of the composite ingredients using spray drying. The role of the additives on glass formation was examined. Characterization revealed multiple novel properties in comparison to the traditional crystalline HE‐based compositions. Differential scanning calorimetry (DSC) analysis showed that in the glassy state the materials have a higher configurational enthalpy, by as much as 42 J g −1 . Thermomechanical analysis (TMA) results indicate that the glassy materials undergo a glass transition at around 50 °C, during which a transformation from a rigid to a liquid‐like state occurs. The glasses showed a tendency to crystallize, as was observed with TMA and DSC analysis. It was observed that the stability of the amorphous phase with respect to crystallization improved with increasing pellet density. These findings serve to highlight the unique opportunity presented by glassy energetics to achieve improvements beyond those attainable with traditional crystalline materials. Abstract :